PENGARUH PENGALAMAN AUDITOR, INDEPENDENSI AUDITOR, DAN SKEPTISME PROFESIONAL TERHADAP AUDIT JUDGMENT - Wiwik Pratiwi; Dhona Nadiya Pratiwi (CURRENT: Jurnal Kajian Akuntansi dan Bisnis Terkini, 2020)
This research aims to test and analyze empirically the effect of auditor experience, auditor independence, and professional skepticism on audit judgment. Respondents in this research was the auditors who work in Public Accountant Office (KAP) in Central Jakarta area. The data collection method uses a questionnaire. The number of auditors that sampled in this research were 140 respondents from 20 Public Accountant Office (KAP) in Central Jakarta. The sampling technique used is convenience nonprobability sampling. Testing instruments were analyzed using validity and reliability tests. The classical assumption test used normality test, multicollinearity test, and heteroscedasticity test. The data analysis technique in this research is multiple linear regression with SPSS version 24. The results of this research showed that the Auditor's Experience, Auditor Independence, and Professional Skeptism have a positive and significant influence on Audit Judgment